1981
DOI: 10.1073/pnas.78.8.4955
|View full text |Cite
|
Sign up to set email alerts
|

Structural and motional changes in glyceraldehyde-3-phosphate dehydrogenase upon binding to the band-3 protein of the erythrocyte membrane examined with [15N,2H]maleimide spin label and electron paramagnetic resonance.

Abstract: Binding of the glycolytic enzyme, glyceraldehyde-3-phosphate dehydrogenase [GAPDHase; D-glyceraldehyde-3-phosphate:NAD+ oxidoreductase (phosphorylating EC 1.2.1.12], to the cytoplasmic segment of band-3 protein in the erythrocyte (RBC) membrane has been examined by electron paramagnetic resonance (EPR) and saturation transfer EPR (ST-EPR) spectroscopies. GAPDHase, which was isolated from rabbit muscle and labeled with the resolution-enhancing deuterated N-(15N-1-oxyl-2,2,6,6-tetramethyl-4-piperidinyl)maleimide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Time-resolved phosphorescence experiments using an antibody to the cytoplasmic domain indicated a highly flexible structure in the region of the binding site (McPherson et al, 1992). ST-EPR studies of spin-labeled hemoglobin (Cassoly, 1982) and spin-labeled glyceraldehyde-3-phosphate dehydrogenase (Beth et al, 1981) bound to the N-terminus of the cytoplasmic domain also suggested that there was considerable motional freedom of this region relative to the hindered rotation of the transmembrane domain.…”
Section: Overview Of Previous Workmentioning
confidence: 97%
“…Time-resolved phosphorescence experiments using an antibody to the cytoplasmic domain indicated a highly flexible structure in the region of the binding site (McPherson et al, 1992). ST-EPR studies of spin-labeled hemoglobin (Cassoly, 1982) and spin-labeled glyceraldehyde-3-phosphate dehydrogenase (Beth et al, 1981) bound to the N-terminus of the cytoplasmic domain also suggested that there was considerable motional freedom of this region relative to the hindered rotation of the transmembrane domain.…”
Section: Overview Of Previous Workmentioning
confidence: 97%
“…The "55 kDa" transmembrane domain (actual molecular weight 59.3 kDa) traverses the bilayer 12 to 14 times thereby forming an anion exchange pathway for chloride and bicarbonate (2). The "41 kDa" cytoplasmic domain of band 3 (cdb3; actual molecular weight 42.5 kDa) serves as an important organizing center for a large number of protein-protein interactions (1,3) including ankyrin (4), protein 4.2 (5), protein 4.1 (6), glycolytic enzymes (7)(8)(9)(10), hemoglobin (11)(12)(13), hemichromes (14), and p72 syk (15). A number of studies carried out over the past two decades have suggested that cdb3 exhibits an elongated, highly asymmetric structure when separated from the transmembrane domain of AE1 as a water soluble protein (16,17) as well as when present in full length AE1 in the erythrocyte membrane (18).…”
Section: Also Known As Band 3 (Reviewed In Ref 1)mentioning
confidence: 99%
“…Istopic substitution of the protons in the spin-label with deuterons reduces inhomogeneous line broadening, increasing the signal-to-noise ratio and the spectral resolution, in particular in the ST-EPR time domain (). Isotopic substitution of 15 N, which has two nuclear spin states, for 14 N, which has three nuclear spin states, simplifies the spectrum, and also increases the signal-to-noise ratio and the spectral resolution ( , ). The earlier EPR study () found that the occupied receptor had a rotational correlation time consistent with smaller oligomers, but was limited in three respects.…”
mentioning
confidence: 99%